2019
DOI: 10.1039/c9ra03087e
|View full text |Cite
|
Sign up to set email alerts
|

Controllable TiO2 coating on the nickel-rich layered cathode through TiCl4 hydrolysis via fluidized bed chemical vapor deposition

Abstract: Surface coating of metal oxides is an effective approach for enhancing the capacity retention of a nickel-rich layered cathode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…During the solvothermal reaction, P123, ethylene glycol and ethanol serves the purpose of co‐surfactant, while P123 play the role of a reducing agent to reduce Ni(CH 3 COO) 2 to nickel and etches the NF surface for the growth of Ni‐OH precursor 46 . In addition, HCl is formed upon decomposition TiCl 4 that further hasten the reduction of nickel and etching of the internal 3D structure of the NF 47,48 . The Ti‐doped Ni‐OH precursor was oxidized to obtain Ti‐doped NiO (denoted NFNTO).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the solvothermal reaction, P123, ethylene glycol and ethanol serves the purpose of co‐surfactant, while P123 play the role of a reducing agent to reduce Ni(CH 3 COO) 2 to nickel and etches the NF surface for the growth of Ni‐OH precursor 46 . In addition, HCl is formed upon decomposition TiCl 4 that further hasten the reduction of nickel and etching of the internal 3D structure of the NF 47,48 . The Ti‐doped Ni‐OH precursor was oxidized to obtain Ti‐doped NiO (denoted NFNTO).…”
Section: Resultsmentioning
confidence: 99%
“…46 In addition, HCl is formed upon decomposition TiCl 4 that further hasten the reduction of nickel and etching of the internal 3D structure of the NF. 47,48 The Ti-doped Ni-OH precursor was oxidized to obtain Ti-doped NiO (denoted NFNTO). Meanwhile, series of controlled sample were also synthesized for detailed synthetic mechanism.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…The popularity of consumer electronics and the rapid development of electric vehicles have put forward higher energy density and longer service life requirements for lithium-ion batteries (LIBs), which are mainly limited by cathode materials. Among the various promising cathode materials, the nickel-rich layered oxides (LiNi x Co y Mn z O 2 , x ≥ 0.6, x + y + z = 1) attract widespread attention due to their extremely high reversible capacity that can even exceed 200 mAh g –1 when the charging voltage exceeds 4.5 V. Except for the contribution of cations, additional capacity is achieved by the redox reaction of anionic oxygen (O 2– /O 2 n – , where 1 < n < 2) during a high charging voltage. , However, Ni-rich materials suffer from severe phase transformation and surface side reactions that cause the capacity and voltage to fade during high-voltage cycling. Therefore, many surface protectors, such as oxides (e.g., Al 2 O 3 , ZrO 2 , TiO 2 ), phosphates (Li 3 PO 4 , FePO 4 , LiFePO 4 ), and fluorides (AlF 3 , LiF, MgF 2 ), were designed to mechanically restrain unwanted structural transformations and inhibit surface side reactions by avoiding direct contact between the cathode materials and the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…10 To be effective, the coating material should (i) not alter the crystal structural of the cathode material, (ii) be thin enough and well-dispersed not to reduce the electrical conductivity, and (iii) prevent degradation of the cathode material. 9,10, 21,22 Table 1 summarizes the electrochemical performance of some surface-modified NCM811 cathode materials at elevated temperatures. 23−30 Among the various materials, TiO 2 has been used as the coating for different cathode materials including NCM523, 31 NCM622, 32 LiMn O 4 , 33 LiNi 0.5 Mn 1.5 O 4 , 34 and LiFePO 4 35 owing to its nontoxic nature, low cost, and thermal/chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the coating strategy is more effective than doping in providing a stable cathode–electrolyte interface and suppressing unwanted side reactions . To be effective, the coating material should (i) not alter the crystal structural of the cathode material, (ii) be thin enough and well-dispersed not to reduce the electrical conductivity, and (iii) prevent degradation of the cathode material. ,,, Table summarizes the electrochemical performance of some surface-modified NCM811 cathode materials at elevated temperatures. Among the various materials, TiO 2 has been used as the coating for different cathode materials including NCM523, NCM622, LiMn 2 O 4 , LiNi 0.5 Mn 1.5 O 4 , and LiFePO 4 owing to its nontoxic nature, low cost, and thermal/chemical stability . Mo et al studied the TiO 2 -coated LiNi 0.6 Co 0.2 Al 0.2 O 2 cathode materials and reported that the presence of TiO 2 coating minimizes the undesired side reaction and stabilizes the structure of NCM622 during charge–discharge cycles.…”
Section: Introductionmentioning
confidence: 99%